Silver Nanoparticles as a Potent Nanopesticide: Toxic Effects and Action Mechanisms on Pest Insects of Agricultural Importance—A Review - Daniel Martínez-Cisterna; Olga Rubilar; Gonzalo Tortella; Lingyun Chen; Manuel Chacón-Fuentes; Marcelo Lizama; Pablo Parra; Leonardo Bardehle (Molecules)
Nanotechnology has been a promising plant protection discipline in recent years, attributed to the unique physicochemical properties exhibited at the nanoscale. In this context, silver nanoparticles (AgNPs) have been effective in various applications, including medical, industrial, and agronomic, and during the last few years, the control of insect pests has raised great interest. The present review mainly provides updated information about the use of AgNPs elaborated by different synthesis methods, such as biological (plants, microorganisms), physical, and chemical, and their effect against various insect species of agricultural importance belonging to the order Diptera, Coleoptera, Lepidoptera, and Hemiptera. The physiological and toxic effects of applying AgNPs are reported and characterized by developmental problems, mortality, weight reduction, interference with enzymatic activity, and anomalies in the life cycle. Moreover, in the final section, the action mechanisms through which AgNPs act on insects are also discussed, highlighting mechanisms such as alteration of transmembrane permeability, interruption of DNA replication, alteration of protein synthesis, and production of reactive oxygen species (ROS).